2009
DOI: 10.4049/jimmunol.0803466
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Proton-Sensing TDAG8 in Extracellular Acidification-Induced Inhibition of Proinflammatory Cytokine Production in Peritoneal Macrophages

Abstract: Extracellular acidification inhibited LPS-induced TNF-α protein production, which was associated with an inhibition of TNF-α mRNA expression, in mouse peritoneal macrophages. The LPS-induced cytokine production was also inhibited by Gs protein-coupled receptor agonists prostaglandin E1 and isoproterenol. Among OGR1 family proton-sensing GTP-binding regulatory protein-coupled receptors, TDAG8, OGR1, and G2A are expressed in the cells. The inhibitory action by acidic pH on TNF-α production was significantly atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 47 publications
9
136
1
Order By: Relevance
“…This cytokine inhibition was shown to occur through the G s -cAMP-protein kinase A (PKA) signaling pathway. 23,27 Treatment with dexamethasone, a potent glucocorticoid, increased GPR65 expression in peritoneal macrophages. Following dexamethasone treatment, there was an inhibition of TNF-α secretion in a manner dependent on increased expression of GPR65.…”
Section: Gpr65 (Tdag8)mentioning
confidence: 99%
See 1 more Smart Citation
“…This cytokine inhibition was shown to occur through the G s -cAMP-protein kinase A (PKA) signaling pathway. 23,27 Treatment with dexamethasone, a potent glucocorticoid, increased GPR65 expression in peritoneal macrophages. Following dexamethasone treatment, there was an inhibition of TNF-α secretion in a manner dependent on increased expression of GPR65.…”
Section: Gpr65 (Tdag8)mentioning
confidence: 99%
“…GPR4, GPR65, and GPR68 play roles in tumor cell apoptosis, proliferation, metastasis, angiogenesis, and immune cell function. 19,27,32,33,44,45,96,97 GPR4 has had conflicting reports in terms of tumor suppressing or promoting activities. One study demonstrated that GPR4 could act as a tumor metastasis suppressor, when overexpressed and activated by acidic pH in B16F10 melanoma cells, by impeding migration and invasion of tumor cells.…”
mentioning
confidence: 99%
“…TDAG8, as well as GPR4, exhibited transforming activities when ectopically overexpressed in immortalized cell lines (Sin et al, 2004). Furthermore, the proton-sensing GPCRs have been shown to regulate immune cell function and inflammatory responses (Ichimonji et al, 2010;Mogi et al, 2009;Onozawa et al, 2011). These observations suggest that the proton-sensing GPCRs may represent novel targets for cancer treatment, inflammation inhibition, and chemoprevention.…”
Section: Molecular Targeting Of Acidosis-related Pathwaysmentioning
confidence: 90%
“…Carbonic anhydrases (CA), monocarboxylate transporters (MCT), vacuolar-type H + -ATPase proton pump (V-ATPase), and sodium/hydrogen exchangers (NHE) play important roles in cellular pH regulation (Izumi et al, 2003;Swietach et al, 2010;Webb et al, 2011). Furthermore, recent studies have shown that a family of protonsensing G protein-coupled receptors regulates the behavior of tumor cells, immune cells, and blood vessels (Ludwig et al, 2003;Mogi et al, 2009;Yang et al, 2007). Targeting these pH regulators may be utilized to kill cancer cells or to augment the effects of other anticancer agents.…”
Section: Molecular Targeting Of Acidosis-related Pathwaysmentioning
confidence: 99%
“…There are some reports of severe metabolic acidemia possibly having caused abnormal cytokinemia that led to permeability pulmonary edema 15,16) . However, the metabolic acidemia in the present neonate was mild and not so severe for his age.…”
Section: Discussionmentioning
confidence: 99%